Invisible China : a journey through ethnic borderlands - Legerton, Colin (Chicago Review Press, 2009)
Explores the minority people who dwell in the farthest reaches of China. This title reveals truths about China's hidden minorities and their complex position in Chinese society through discussions, including a debate with Ewenki village cadres on human rights and talks with ageing hajjis about the Chinese government's razing of their mosque.